DIABETIC KETOACIDOSIS MANAGEMENT IN HOSPITAL SULTAN HAJI AHMAD SHAH (HOSHAS): A CLINICAL AUDIT - Fazial, Nur Shairah Binti Mohamad; Shudim, Saiful Shahrizal; Keong, See Chee (Journal of the ASEAN Federation of Endocrine Societies, 2025)
INTRODUCTION Diabetic ketoacidosis (DKA) is a serious condition and improper initial assessment and management may lead to undesirable outcomes and even death. This clinical audit aimed to evaluate adherence to DKA management in HoSHAS according to standardized national and local guidelines. The standards pre-determine by local standards were: (1) Severe DKA patients should be managed in an ICU/HDW setting; (2) All patients should be treated according to standardized guidelines (fluid and insulin therapy, observation) and achieve resolution of DKA within 24 hours of diagnosis; (3) All patients should be assessed by diabetes educators prior to discharge; (4) All patients should have a well-documented discharge and follow-up plan. METHODOLOGY This audit was conducted from November to December 2024, involving all adult patients (aged 18 years and above) who met the diagnostic criteria for DKA. Patients with concurrent cardiac disease, ESRD, elderly patients, and pregnancy were excluded. Patient demographics and clinical data were collected from electronic medical records. RESULT Thirty patients were included with predominant male (56.7%) and Malay ethnicity (90%) and median age of 54 years. Majority had underlying T2DM (93.3%) and presented with sepsis (96.7%). The median length of hospital stay was 5.5 days. 33.3% of patients had severe DKA, but only 30% were managed in an ICU/HDW setting. All patients were treated according to standardized guidelines and had resolution of DKA within 24 hours. Only (55.5%) of patients were assessed by diabetes educators before discharge. Majority of patients had a well-documented discharge plan, but only (70%) had follow-up care arranged within the hospital. CONCLUSION The audit revealed good adherence to standardized DKA management protocols. However, there is room for improvement in the prioritization of severe DKA cases for ICU/HDW admission. The importance of diabetes educators in the post-recovery phase of DKA should be better recognized, and follow-up care process needs to be enhanced.